2001
DOI: 10.1002/clc.4960241109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients with coronary artery disease by assessing diastolic abnormalities during isometric exercise

Abstract: Background: Previous clinical studies using invasive and noninvasive methods have shown handgrip‐induced diastolic abnormalities in patients with coronary artery disease (CAD). Hypothesis: The study was undertaken to determine the utility of Doppler echo‐ and pressocardiography during handgrip in discriminating patients with coronary artery disease (CAD) and in those with normal coronary arteries. Methods: Both methods were obtained in 96 patients with suspected CAD within 24 h before coronary angiography. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…It has been shown that these recordings reflect unidirectionally corresponding temporal and amplitude changes of the LVP curve both at rest [15-23] and during exercise [24-26]. A high-magnitude increase of the pressocardiographic relative/“pulse” A wave amplitude has been shown with exercise [24-35] in CAD patients, which was very similar to the corresponding dramatic LVEDP rise in the presence of ischemia. …”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…It has been shown that these recordings reflect unidirectionally corresponding temporal and amplitude changes of the LVP curve both at rest [15-23] and during exercise [24-26]. A high-magnitude increase of the pressocardiographic relative/“pulse” A wave amplitude has been shown with exercise [24-35] in CAD patients, which was very similar to the corresponding dramatic LVEDP rise in the presence of ischemia. …”
Section: Introductionmentioning
confidence: 83%
“…In patients with angiographically verified CAD, a positive presso test (ischemic or non-ischemic) has been found in 86-93% of outpatients [30-34] and 95% of hospitalized patients with CAD [35]. Moreover, patients with hypertension [41, 42], hypertrophic cardiomyopathy [43, 44] and syndrome X [45] showed a positive presso test in 70%, 95% and 100%, respectively.…”
Section: Noninvasive Assessment Of Ischemic Diastolic Response Using mentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Manolas correctly identifies the use of invasive pressure measurements in our approach as a limitation and proposes to replace the invasive pressure measurements by "pressocardiograms." The feasibility of this approach, by using the pressocardiography during hand-grip exercise, was examined in several studies by Manolas et al (4). The pressocardiograms resemble ventricular pressure tracings and have been used to quantify the timing of cardiac events during the cardiac cycle.…”
Section: R E P L Ymentioning
confidence: 99%
“…Die bessere [27,28]. Der "hand grip" ist eine einfache und hilfreiche Form der Belastung in der täglichen Routine [29][30][31]. Verschiedene Leitlinien stehen zur Verfügung, die ausführlich auf die technische Durchführung eingehen [32,33].…”
unclassified